2007
DOI: 10.1042/ba20060216
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the glycosylation profile of a monoclonal antibody produced by hybridomas cultured in serum‐supplemented, serum‐free or chemically defined media

Abstract: SFM (serum-free medium) is preferred to media containing animal-derived components when culturing mammalian cells for the production of therapeutic recombinant proteins and mAbs (monoclonal antibodies). Nonetheless, eliminating animal-derived components from media can strongly modify culture performance and alter protein glycosylation. In the present study, mAb glycosylation profiles, extracellular exoglycosidase activities, hybridoma growth and mAb production in traditional medium containing 10% (v/v) FBS (fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 52 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Known as functional elements, these include galactose, core fucose, and sialic acid, and have been shown to influence antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). In fact higher levels of galactosylation (Abès and Teillaud 2010; Hodoniczky et al 2005; Jefferis and Lund 1997; Serrato et al 2007), reduced core fucosylation (Shields et al 2002; Shinkawa et al 2003; Sibéril et al 2006) or reduced sialylation (Anthony and Ravetch 2010; Anthony et al 2008; Kaneko et al 2006; Scallon et al 2007) are suggested to enhance the clinical efficacy of mAbs that exert their therapeutic effect by ADCC and CDC mediated killing, such as those used for cancer treatment, including the mAb here assessed. This is particularly relevant for core fucosylation, whose absence can improve ADCC activity by up to 100-fold (Shields et al 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Known as functional elements, these include galactose, core fucose, and sialic acid, and have been shown to influence antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). In fact higher levels of galactosylation (Abès and Teillaud 2010; Hodoniczky et al 2005; Jefferis and Lund 1997; Serrato et al 2007), reduced core fucosylation (Shields et al 2002; Shinkawa et al 2003; Sibéril et al 2006) or reduced sialylation (Anthony and Ravetch 2010; Anthony et al 2008; Kaneko et al 2006; Scallon et al 2007) are suggested to enhance the clinical efficacy of mAbs that exert their therapeutic effect by ADCC and CDC mediated killing, such as those used for cancer treatment, including the mAb here assessed. This is particularly relevant for core fucosylation, whose absence can improve ADCC activity by up to 100-fold (Shields et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, it has been shown that CHO cells produce an extracellular sialidase capable of modifying the sialic acid content of glycoproteins (Gramer and Goochee 1993), and the production/accumulation of this enzyme may be influenced by culture conditions, therefore affecting the degree of sialylation. Additionally, it should be noted that the reported degree of sialylation in human IgG has been below 20% (Arnold et al 2007; Pučić et al 2011; Serrato et al 2007), but some of the microcarrier cultures showed superior levels (e.g. CY2), mainly due to a higher prevalence of disialylated (S2) structures, both digalacto (S2G2) and trigalacto (S2G3), with potential negative effects on mAb activity by reducing ADCC.…”
Section: Resultsmentioning
confidence: 99%
“…Such differences can also have a substantial effect on degradative processes affecting shelf-life, such as susceptibility to oxidation, deamidation, and aggregation. [5][6][7][8][9] There are many analytical methods that can be used to assess the similarity between biosimilars and their reference products in the early stages of development. These methods can be classified according to quality attributes that they measure such as structural characterization (primary and higher order), purity (product and manufacturing process related), assessment of glycan profile, and biological activity (eg, binding assays).…”
Section: Introductionmentioning
confidence: 99%
“…More so, CHO cell lines have shown to be stable, scalable, high-yield protein expression platforms with proper post-translational processing capabilities for several therapeutic applications (Nolan and Lee, 2011;Rodrigues et al, 2012;Kildegaard et al, 2013). However, productivity optimization is challenging, due to the intricate cellular machinery, compartmentalized metabolism and complex regulation and interconnection between multiple biological and media components that determine not only product quantity, but also quality (Palomares et al, 2004;Serrato et al, 2007;Hagrot et al, 2015). Systematic screening and derived statistical information have been useful, but often do not offer any insight on cell metabolism and regulation, making the exploration of multiple process and genetic modification targets difficult to assess and perform (Nolan and Lee, 2012;Hagrot et al, 2015).…”
Section: Introductionmentioning
confidence: 99%